بإ قليم دار فور في السودان دور الطرق الصوفية في إحلال الأمن والسلام - Muhammad Rifa'i Mohd Amin; Rajab Muhammad Asyatibah (Universiti Sains Islam Malaysia, 2024)
lslam is a religion of peace and security. It imposes many rules that guarantees peacefulness of human life. The difference of thought is the nature of the people. This will reach some people to the extent of fighting between two different groups. lslam asked to reconcile between the two disputed Muslim groups. This research focuses on the efforts of Sufi orders in Darfur, west Sudan, in reaching a peaceful solution for the conflict which have claimed many lives. This study aims to reveal the role of Sufi Orders and their influence in Sudanese society. The method employed is the library research method with a case study. The finding of research prove the influence of Sufi Sheikh's and Orders in the ordinary lives of the people in Sudan and their involvement in solving social and political problems among the Muslims.